(3GdMGad GdhSjW hGdYjde GdRGNQ GdeMjW aj CMhGd GdChGFd hGdChGNQs - (3eUWai Hf MSf Hf SfGf Hf CMeO GdMSjfj GdgGTej, CHh eMeO GdLfGHj, Ke GdQhej,J (B999 (3g` s
(3ChdgG (B:s
(3pCTQa cdGe jJVhY fTQg hQjGg s
(3QJHg GdeDda Ydi ebOeI hGKfjJf HGHkG cd HGH ai OhdIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B231 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B246s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B300 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B113 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B291s
Keywords: (3GdJGQjNs